The Customer Journey in Purchasing Counterfeit Fashion Among Generation Z - Purwati, Yenny; Widodo, Arief (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: The study aims to explore how digital technologies redefine the customer journey of generation Z, particularly on their experiences purchasing counterfeit fashion products. Design/Method/Approach: This study employs the quantitative descriptive analysis technique. A survey was administered generation Z who have prior experience in purchasing counterfeit fashion items. Research Finding: The findings reveal that online marketplace and social media play an important role in generation Z’s journey for counterfeit fashion. These two platforms not only increase awareness and appeal stages through advertisement and recommendation but also enable direct interaction and digital transactions. Theoretical contribution/Originality: This study contributes to a relatively unexplored topic in developing countries like Indonesia, especially about customer journey and counterfeit purchases. Practitioner/Policy implication: This study offers insights to policymakers and fashion industry stakeholders. An understanding of customer journey can help policymakers to advocate for policy regarding the ethics of counterfeit purchases. Additionally, the findings can assist fashion industry stakeholders in promoting the value of authentic products. Research limitation: This study primarily focused on generation Z, hence limits its applicability to other demographic groups.